3-6+12=9
Steps
you have to add first so you must add -6+12 which will be -6
Then you will take 3 - - 6 which will make it 9
Answer:
see explanation
Step-by-step explanation:
Assuming you require to factorise the expressions
16
- 12
+ 4y ← factor out 4y from each term
= 4y(4
- 3y³ + 1)
--------------------------------
64ax² - 49ay² ← factor out a from each term
= a(64x² - 49y²) ← this is a difference of squares and factors in general as
a² - b² = (a - b)(a + b) , then
64x² - 49y²
= (8x)² - (7y)²
= (8x - 7y)(8x + 7y)
then
64ax² - 49ay² = a(8x - 7y)(8x + 7y)
Only graph the rational numbers and draw a line to account for the rest of them
Answer:
true
Step-by-step explanation:
Answer:
18 arms
Step-by-step explanation:
12÷8=1.8
10×1.8=18